MEMBANGUN ALTRUISME PADA SISWA SMP BUSTANUL MAKMUR GENTENG BANYUWANGI - Imam Mashuri; Imam Wahyono; Eka Ramiati (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Altruism is behavior and voluntary help that departs from a sincere heart, which is positive, and without and beneficial to others. Entering Era 4.0 makes some people behave selfishly, selfishly and don't care about others. This is a challenge for parents and teachers as educators, to build altruime attitudes in children from an early age, one of which is through the school environment.